Using a Novel Grey System Model to Forecast Natural Gas Consumption in China. (15th January 2015) - Wu, Lifeng; Liu, Sifeng; Chen, Haijun; Zhang, Na
Abstract : Accurate prediction of the future energy needs is crucial for energy management. This work presents a novel grey forecasting model that integrates the principle of new information priority into accumulated generation. This grey model can better reflect the priority of the new information theoretically. The results of two practical examples demonstrate that this grey model provides very remarkable short-term predication performance compared with traditional grey forecasting model for limited data set forecasting. It is applied to Chinese gas consumption forecasting to show its superiority and applicability.